Learning Environment Variables and the Efficacy of Student Learning in Secondary School in Abak Local Government, Akwa Ibom State - Oladeni Sakirudeen, Abisola; Uwe, Ekanem (Revija za elementarno izobraževanje, 2020)
Four research questions and four null hypotheses were formulated to guide the study. A simple random sampling technique was used in selecting 34 respondents from each 6 schools, with a sample size of 204 was selected from the population of 1,518. The instrument titled LEVSLEQ was used to elicit response from the respondent. The reliability of the research instrument yielded a co-efficient of 0.82. The data was analyzed using dependent t-test and was tested at .05 level of significance. The findings indicated that environmental variable studied influence students’ learning effectiveness.